Pengaruh Suku Bunga, Return On Assets, Dan Debt To Equity Ratio Terhadap Nilai Perusahaan Melalui Harga Saham Sebagai Variabel Intervening Pada Perusahaan Energi Di Bursa Efek Indonesia Periode 2021-2024 - Mardho Tillahi Assalam; Elfiswandi .; Putri Intan Permata Sari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of interest rates, Return on Assets (ROA), and Debt to Equity Ratio (DER) on firm value with stock price as an intervening variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. The sample was selected using a purposive sampling method to obtain companies that met the research criteria. The data analysis methods employed include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis and path analysis. The results indicate that interest rates do not have a significant effect on stock prices or firm value. Return on Assets (ROA) and Debt to Equity Ratio (DER) have a positive and significant effect on firm value. Furthermore, stock price does not have a significant effect on firm value and therefore does not mediate the relationship between ROA and firm value, nor between DER and firm value. Thus, stock price does not function as an intervening variable in this study. Based on these findings, future research is recommended to extend the observation period and include additional variables that may influence firm value in order to obtain more comprehensive results.